A Study of Job Satisfaction among Civil Engineers Working in Hydropower Sector in Consulting Firms - Thapa, Prabin; Shrestha, Santosh Kumar (Journal of the Institute of Engineering, 2018)
An increase in job satisfaction is directly related to an increase in productivity. The study was conducted with the aim of finding job satisfaction of civil engineers working in hydropower sector in consulting firms of Nepal. Descriptive cross sectional study was conducted among civil engineers in 34 consulting firms. Self-administered questionnaire were distributed among 230 civil engineers where 143 respondents had replied in time. Collected data was analyzed using descriptive as well as inferential statistical method. Study finding shows that on an average, the job satisfaction score of employees was 3.69 out of 5 with standard deviation of 0.63 coefficient of variance equals to 0.17. Similarly, relationship of Job satisfaction by both method (single global rating method and summation job factors method) with independent variables shows that pay systems (0.424 and 0.642), job itself (0.334 and 0.650), relation with supervisors (0.312 and 0.637), working conditions (0.296 and 0.628) and promotion opportunities (0.273 and 0.757) were positively related with overall job satisfaction at 95 % confidence level. Based on finding of the study, it can be concluded that, the majorities of civil engineers were satisfied with their job despite their low rating on pay and promotion opportunities. The management of consulting firms and concerned authorities should focus on improving pay and promotions opportunities and designing proper programs for further improvement of job satisfaction. Journal of the Institute of Engineering, 2018, 14(1): 165-169